2018
DOI: 10.1167/tvst.7.5.35
|View full text |Cite
|
Sign up to set email alerts
|

Improving Spatial Resolution and Test Times of Visual Field Testing Using ARREST

Abstract: PurposeCorrectly classifying progression in moderate to advanced glaucoma is difficult. Pointwise visual field test–retest variability is high for sensitivities below approximately 20 dB; hence, reliably detecting progression requires many test repeats. We developed a testing approach that does not attempt to threshold accurately in areas with high variability, but instead expends presentations increasing spatial fidelity.MethodsOur visual field procedure Australian Reduced Range Extended Spatial Test (ARREST;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
28
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(28 citation statements)
references
References 25 publications
0
28
0
Order By: Relevance
“…The locations of the projected VF stimuli were corrected for lateral displacement of GCs relative to the underlying stimulated photoreceptors due to elongation of Henle fibers at the central fovea 16 , 20 , as per Drasdo et al’s Fig. 6 27 and consistent with previous studies applying this methodology 7 , 16 , 18 , 33 . Irrespective of individual fovea to optic disc tilts, the VF-based paradigms were maintained at a tilt of 0° to maintain consistency with natural head positioning during VF testing and therefore ensure that structural measurements were accurately extracted over retinal locations stimulated by VF test points (Fig.…”
Section: Methodsmentioning
confidence: 67%
“…The locations of the projected VF stimuli were corrected for lateral displacement of GCs relative to the underlying stimulated photoreceptors due to elongation of Henle fibers at the central fovea 16 , 20 , as per Drasdo et al’s Fig. 6 27 and consistent with previous studies applying this methodology 7 , 16 , 18 , 33 . Irrespective of individual fovea to optic disc tilts, the VF-based paradigms were maintained at a tilt of 0° to maintain consistency with natural head positioning during VF testing and therefore ensure that structural measurements were accurately extracted over retinal locations stimulated by VF test points (Fig.…”
Section: Methodsmentioning
confidence: 67%
“…8 ARREST is designed to add additional locations in areas of steep visual field gradient without increasing test duration. 3 Second, current test procedures repeatedly assess perimetrically blind locations at each subsequent test visit. Testing locations that are well established to be at the measurement floor (0 dB) provides no additional information.…”
Section: Introductionmentioning
confidence: 99%
“…ARREST does not retest locations with established sensitivity of < 0 dB. 3 The third limitation of current procedures is the well-studied higher test-retest variability in moderate and advanced visual field loss, [11][12][13][14][15][16] which reduces the accuracy of sensitivity estimates. Recently, Gardiner et al 16 have shown that testing locations with sensitivity below approximately 15 to 19 dB with current SAP implementations does not provide information that is particularly clinically useful due to the degree of measurement noise.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations